Nasal priming with immunobiotic Lactobacillus rhamnosus modulates inflammation–coagulation interactions and reduces influenza virus-associated pulmonary damage - Zelaya, María Hortensia del Rosario (2015)
Objective: To evaluate the effect of the nasal administration of live and heat-killed Lactobacillus rhamnosus CRL1505 (Lr1505) on immune-coagulative response during influenza virus (IFV) infection to improve survival and reduce lung injury. Methods: Six-week-old BALB/c mice were treated with live or heat-killed Lr1505 by the nasal route during two consecutive days. Treated and untreated control mice were then nasally challenged with IFV. Results: Both viable and non-viable Lr1505 protected infected mice by reducing pulmonary injury and lung viral loads trough several mechanisms: (a) Inflammatory cytokines were efficiently regulated allowing higher clearance of virus and reduction of inflammatory lung tissue damage, associated to higher levels of the regulatory cytokine IL-10. (b) The antiviral immune response was enhanced with improved levels of type I interferons, CD4+IFN-g+ lymphocytes, and lung CD11c+CD11blow- CD103+ and CD11c+CD11bhighCD103- dendritic cells. (c) The procoagulant state was reversed mainly by downregulating tissue factor expression and restoring thrombomodulin levels in lung. The capacity of Lr1505 to improve the outcome of IFV infection would be related to its ability to beneficially modulate lung TLR3-triggered immune response. Conclusions: Our work is the first to demonstrate the ability of an immunobiotic strain to beneficially modulate inflammation-coagulation interactions during IFV infection. Interestingly, non-viable L. rhamnosus CRL1505 was as effective as the viable strain to beneficially modulate respiratory antiviral immune response.